Creative Destinations and Heritage Interpretation: The Story of Transilvania Creative Camp 2016 - Nechita, Florin; Tanaka, Hiromasa (Presa Universitară Clujeană, 2017)
This book sets out to be a mostly visual story of the Transilvania Creative Camp - Creative Destinations and Heritage Interpretation Summer School, a project that combined creative and cultural tourism with anthropology research, digital media and destinations communication. After the first edition was set out in various location in Brasov county, the current edition successfully revealed Lapus Land, a dreamlike place from the Maramures county, northwestern Transylvania. The 26 students from Romania, Japan and Italy, together with 12 faculty members and communication professionals, 2 representatives of the Tourism Information Center Targu Lapus explored the area in order to find insights for promotion of this destination. During the 6 full days of the creative summer camp, the participants managed to combine workshops and presentations a with actively experiencing the daily life in the villages in Lapus Land.
Keywords: creative destinations; heritage interpretation; project-based learning